2020
DOI: 10.1097/cj9.0000000000000139
|View full text |Cite
|
Sign up to set email alerts
|

Successful rescue with videolaryngoscopy after failed fibroscopy in anticipated difficult airway: case series

Abstract: Introduction: In the management of the anticipated difficult airway (DA), awake intubation is the strategy of choice. In this context, flexible fibroscopy is the tool most widely used as the first choice. However, there is always the rare case where it may fail. Important findings: Six successful rescue cases using videolaryngoscopy following failed fibroscopy in patients with anticipated DA, and 1 case of rescued extubation of an airway previously secured with fiberoptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[488][489][490][491] Case reports also observed successful intubation with videolaryngoscopes in unanticipated and emergency difficult airways (Category B4-B evidence). 160,[492][493][494][495][496] A retrospective observational study reported a flexible bronchoscopy success rate of 78% for intubation rescue after failed direct laryngoscopy (Category B3-B evidence). 488 Case reports of flexible bronchoscopy or fiberoptic **** Any one factor alone (i.e., assessed difficulty with intubation or ventilation, increased risk of aspiration or desaturation) may be of sufficient clinical importance to warrant an awake intubation.…”
Section: Recommendations For Anticipated Difficult Airway Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…[488][489][490][491] Case reports also observed successful intubation with videolaryngoscopes in unanticipated and emergency difficult airways (Category B4-B evidence). 160,[492][493][494][495][496] A retrospective observational study reported a flexible bronchoscopy success rate of 78% for intubation rescue after failed direct laryngoscopy (Category B3-B evidence). 488 Case reports of flexible bronchoscopy or fiberoptic **** Any one factor alone (i.e., assessed difficulty with intubation or ventilation, increased risk of aspiration or desaturation) may be of sufficient clinical importance to warrant an awake intubation.…”
Section: Recommendations For Anticipated Difficult Airway Managementmentioning
confidence: 99%
“…488–491 Case reports also observed successful intubation with videolaryngoscopes in unanticipated and emergency difficult airways (Category B4-B evidence ). 160,492–496 A retrospective observational study reported a flexible bronchoscopy success rate of 78% for intubation rescue after failed direct laryngoscopy (Category B3-B evidence ). 488 Case reports of flexible bronchoscopy or fiberoptic nasotracheal intubation observed successful rescue intubations for unanticipated and emergency difficult airways (Category B4-B evidence ).…”
Section: Unanticipated and Emergency Difficult Airway Managementmentioning
confidence: 99%
“…5 There has been several reports on failed fiberoptic intubation needing alternative plans. 5,6 In most of the situations, the backup plan would be to perform a tracheostomy under local anesthesia. In this patient, performing a tracheostomy would have been difficult due to previous tracheostomy.…”
Section: Discussionmentioning
confidence: 99%